2021
DOI: 10.2196/26732
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-Created Educational Video Resources for Shared Decision-making in the Outpatient Management of Chronic Disease: Development and Evaluation Study

Abstract: Background The provision of reliable patient education is essential for shared decision-making. However, many clinicians are reluctant to use commonly available resources, as they are generic and may contain information of insufficient quality. Clinician-created educational materials, accessed during the waiting time prior to consultation, can potentially benefit clinical practice if developed in a time- and resource-efficient manner. Objective The aim … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The provision of reliable patient education is essential for shared decision-making. The consultation/reading of educational materials, accessed during the waiting time prior to consultation or prescription medicine supply (hospital pharmacy), can potentially benefit clinical practice if implemented in a time- and resource-efficient manner [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The provision of reliable patient education is essential for shared decision-making. The consultation/reading of educational materials, accessed during the waiting time prior to consultation or prescription medicine supply (hospital pharmacy), can potentially benefit clinical practice if implemented in a time- and resource-efficient manner [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is to provide clinician-created educational videos about vaccines that include answers to frequently asked questions. This strategy has been successfully used in managing chronic diseases and could be used with immunizations (Kovoor et al, 2021). Alternately, a clinic could hire a registered nurse immunization educator who is solely responsible for tracking, implementing, and performing t vaccine education and administration.…”
Section: Implications For Nurse Practitionersmentioning
confidence: 99%
“…All patients were satisfied with the video which helped them to remember the information given by the nurse. In 2021, JG Kovoor et al showed clinician-created educational videos of atrial fibrillation in improving patient decision-making ability, long-term treatment adherence, and anxiety reduction [28]. In this study, we created the education video of acne as a PDA to implement SDM at clinics.…”
Section: Plos Onementioning
confidence: 99%